The year in television, 2008 a catalog of new and continuing series, miniseries, specials and TV movies - Terrace, Vincent, 1948- (McFarland & Co., Publishers, 2009)
"This reference book covers all the first run entertainment programs broadcast over the airwaves and on cable from January 1 through December 31, 2008, including series, specials, miniseries, made-for-television movies, pilot films, Internet series and specialized series (those broadcast on gay and lesbian channels)"--Provided by publisher.